Serum 25-hydroxyvitamin D3 and body composition in an elderly cohort from Germany : a cross-sectional study - Jungert, Alexandra; Roth, Heinz; Neuhauser-Berthold, Monika; Justus Liebig University Giessen (My University, 2012)
BACKGROUND: Emerging evidence indicates that there is an association between vitamin D and obesity. The aim of this study was to investigate whether the level of serum 25-hydroxyvitamin D3 [25(OH)D3] in the elderly is influenced by parameters of anthropometry and body composition independent of potential confounding lifestyle factors and the level of serum intact parathyroid hormone (iPTH). METHODS: Cross-sectional data of 131 independently living participants (90 women, 41 men; aged 66-96years) of the longitudinal study on nutrition and health status in senior citizens of Giessen, Germany were analysed. Concentrations of 25(OH)D3 and iPTH were ascertained by an electrochemiluminescence immunoassay. Body composition was measured by a bioelectrical impedance analysis. We performed univariate and multiple regression analyses to examine the influence of body composition on 25(OH)D3 with adjustments for age, iPTH and lifestyle factors. RESULTS: In univariate regression analyses, 25(OH)D3 was associated with body mass index (BMI), hip circumference and total body fat (TBF) in women, but not in men. Using multiple regression analyses, TBF was shown to be a negative predictor of 25(OH)D3 levels in women even after controlling for age, lifestyle and iPTH (SZ=0.247; P=0.016), whereas the associations between BMI, hip circumference and 25(OH)D3 lost statistical significance after adjusting for iPTH. In men, 25(OH)D3 was not affected by anthropometric or body composition variables. CONCLUSIONS: The results indicate that 25(OH)D3 levels are affected by TBF, especially in elderly women, independent of lifestyle factors and iPTH.
Keywords: 25-hydroxyvitamin D3; obesity; total body fat (TBF); elderly women; ddc:610